COMPARATIVE ANALYSIS OF TRENDS, GROWTH, AND INSTABILITY IN THE AREA, PRODUCTION, AND YIELD OF MAIZE IN BIHAR AND KARNATAKA - RAVI KUMAR; PUSHPA M. SAVADATTI (The Journal of Research ANGRAU, 2024)
The present study has attempted in the year 2022 to analyze maize production trends, growth, and instability in Bihar and Karnataka. Average, Compound Annual Groth Rate (CAGR), and Cuddy Della Valley Index (CDVI) were employed to essess the data from 2002 to 2003 and 2021 to 2022, divided into three periods. As far as kharif maize’s average trend and CAGR of area, production, and yield were concerned, it was dominated by Karnataka during all the periods. For rabi maize, it was dominated by Bihar for the same, but its yield was less than the nation’s yield during both seasons. In case of India, kharif maize’s area and production were much more than the rabi maize, but the yield was low during the entire period for the same. It was also revealed that production growth was due to both the area and yield growth. However, the yield effect was highly significant during all the periods for all the seasons for Bihar, Karnataka, and India. Instability in production for the entire period was more, i.e., 31.32 in Bihar during the kharif season, and it was more in Karnataka, i.e., 22.38 during the rabi season.